Octreotide Infusion for the Treatment of Congenital Chylothorax - Sumayyah Ahmed Nezar Kobeisy; Abdulaziz Alkhotani; Mohammed M. Barzanji (Case Reports in Pediatrics)
Congenital chylothorax is an uncommon cause of pleural effusion in the pediatric age group, and it should be kept in consideration when evaluating a neonate with pleural effusion, as it is the commonest cause of pleural effusion in this age group (Tutor, 2014). No commonly accepted guidelines have been published so far regarding the management of congenital chylothorax in the neonate, but trials of octreotide have appeared to be promising (Bellini et al., 2018). We present a neonate with congenital chylothorax successfully treated with octreotide infusion.